Bridging the Gap: Profiling Environmental Literacy Dimensions among Pre-Service Chemistry Teachers - Ayu Ashari; Faathir Almur (Science Education and Application Journal, 2026)
This study aims to measure the environmental literacy of prospective chemistry teacher students, focusing on three main aspects: knowledge, attitudes, and behavior. This study was conducted on prospective chemistry teacher students from a state university in Makassar. The study population was all students from the class of 2025, consisting of six classes. The sample was selected using purposive sampling based on the criteria of students currently studying chemistry education. The sample size of this study involved 73 prospective chemistry teacher students from three classes of the class of 2025. Data collection was conducted using a questionnaire distributed to prospective chemistry teacher students via Google Form. The data collection instrument met the reliability test with a value of >0.70 using the Cronbach Alpha test and obtained the knowledge aspect with a value of 0.935, attitude with a value of 0.913, and behavior with 0.873. The data obtained were analyzed using descriptive statistical analysis. The results showed that the knowledge aspect had an average score of 64.27% in the medium category. The student attitude aspect obtained an average score of 79.04%, which is in the high category. Meanwhile, for behavior, the average score of 81.48% is in the high category. Although students have positive attitudes toward sustainability and are beginning to adopt pro-environmental behaviors, a gap remains between knowledge and behavior. This research recommends strengthening the chemistry curriculum and conducting research on improving environmental literacy, particularly in the knowledge aspect. Furthermore, a qualitative study is needed to determine why behavior is significantly higher than knowledge.